2017
DOI: 10.4103/2279-042x.200993
|View full text |Cite|
|
Sign up to set email alerts
|

A copmarative review of electronic prescription systems: Lessons learned from developed countries

Abstract: This review study aimed to compare the electronic prescription systems in five selected countries (Denmark, Finland, Sweden, England, and the United States). Compared developed countries were selected by the identified selection process from the countries that have electronic prescription systems. Required data were collected by searching the valid databases, most widely used search engines, and visiting websites related to the national electronic prescription system of each country and also sending E-mails to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…The EMR e-prescribing system allows me to create new prescriptions 48 (16) 45 (15) 213 70The EMR e-prescribing system allows me to detect prescribing errors 74 (24) 77 (25) 155 51The EMR e-prescribing system allows me to receive medication interaction alerts 162 (53) 44 (14) 100 33The EMR e-prescribing system allows me to receive medication allergy alerts 41 (13) 34 (11) 231 (75)…”
Section: Functionalitymentioning
confidence: 99%
See 2 more Smart Citations
“…The EMR e-prescribing system allows me to create new prescriptions 48 (16) 45 (15) 213 70The EMR e-prescribing system allows me to detect prescribing errors 74 (24) 77 (25) 155 51The EMR e-prescribing system allows me to receive medication interaction alerts 162 (53) 44 (14) 100 33The EMR e-prescribing system allows me to receive medication allergy alerts 41 (13) 34 (11) 231 (75)…”
Section: Functionalitymentioning
confidence: 99%
“…[8][9][10] The successful adoption of e-prescribing systems has been reported in many regions worldwide, including the USA, UK, European Union and Canada. 10,11 The main barriers to implementation include cost, time, lack of efficiency, negative perceptions of technology and its impact on care, lack of prior experience with computers, low computer literacy, limitations in interoperability, difficulty of data entry/ correction and the ability of the system to complete desired tasks. [11][12][13][14][15] Furthermore, there may be concerns regarding differences in healthcare policies and the enforcement of local privacy and data protection laws.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3. The result of this research suggest that involving real users in the service or system design from the initial stages and throughout the development life cycle could help enhance usability and user experiences, or at least flag up cases in which national policy will be detrimental to local activities From another study in Iran, Ahmadi, Samadbeik, & Sadoughi (2014) shows that the results of the process documentation were analyzed using a conceptual model of workflow elements and the technique of modeling "As-Is" business processes. Analysis of the current (as-is) prescribing process demonstrated that Iran stood at the first levels of sophistication in graduated levels of electronic prescribing, namely electronic prescription reference, and that there were problematic areas including bottlenecks, redundant and duplicated work, concentration of decision nodes, and communicative weaknesses among stakeholders of the process.…”
Section: Figure 1 Flowchart Of Prisma Methodsmentioning
confidence: 99%
“…6 of Journal of Research in Pharmacy Practice,[1] the spelling of the word “Comparative” is written incorrectly in the article title as “Copmarative”. The correct article title should appear as “A Comparative Review of Electronic Prescription Systems: Lessons Learned from Developed Countries”.…”
mentioning
confidence: 99%